AIM2 Co-immunization with VP1 Is Associated with Increased Memory CD8 T Cells and Mounts Long Lasting Protection against Coxsackievirus B3 Challenge - Yin, Liang; Chai, Dafei; Yue, Yan; Dong, Chunsheng; Xiong, Sidong (Frontiers in Cellular and Infection Microbiology, 2017)
The recurrent Coxsackievirus B3 (CVB3) infection is the most important cause of intractable myocarditis which often leads to chronic myocarditis and even dilated cardiomyopathy. Therefore, enhanced DNA vaccines capable of memory CD8 T cells are essential for long-lasting immunological protection against CVB3 infection. In this study, absent in melanoma 2 (AIM2) was used as an adjuvant to enhance the induction of memory CD8 T cells elicited by VP1 (viral capsid protein 1) vaccine. Mice were intramuscularly injected with 50μg AIM2 plasmid and equal amount of VP1 plasmid (pAIM2/pVP1) vaccine 4 times at 2 week-intervals. We observed that the protection of pAIM2/pVP1 vaccine against CVB3 challenge was evidenced by significantly improved cardiac function, reduced myocardial injuries, and increased survival rate when compared with immunization with pVP1. Co-immunization with pAIM2/pVP1 robustly augmented T lymphocytes proliferation and CVB3-specific cytotoxic T lymphocyte responses. Importantly, 16 weeks after the last immunization, pAIM2/pVP1 co-immunization significantly enhanced the expression of Bcl-6, SOCS3, and Sca-1 which are critical for memory CD8 T cells as compared with pVP1 immunization. Notably, CD8 T cells that are likely vaccine-induced memory T cells were responsible for the protective efficacy of pAIM2/pVP1 vaccine by abolition of a CD8 T cell immune response following a lethal dose of CVB3 infection. Our results indicate that AIM2-adjuvanted vaccine could be a potential and promising approach to promote a long-lasting protection against CVB3-induced myocarditis.